TRANSLATION OF CHILDREN’S STORYBOOK FROM THE SKOPOS THEORY PERSPECTIVE - Siti Luruh Ayu Noerjanah (IAIN Syekh Nurjati Cirebon, 2017)
Abstract. This study investigated the strategies applied by the translator in translating a series of bilingual children storybook (Indonesia-English) entitled: Kancil Jadi Raja (Mouse Deer Becomes King) published by Dinar Media, Jakarta and the appropriateness of the translation result with Skopos theory. This study employed a descriptive qualitative study design. Total sampling was applied to collect the data. The data were collected from the texts of the bilingual children’s storybook or document analysis. The researcher analysed the documents using the microstructural analysis introduced by Leuven Zwart (1989-1990), an expert in translation studies which developed a comparative model of texts analysis, where the source texts and target texts was compared to identify the translation strategies, The texts consist of 59 sentences. The data shows that: 1.) There were eleven (11) types of translation strategies applied by the translator which was in line with skopos theory or more likely to emphasized on the Target Text (TT), among others: Transference strategy applied six (6) times , Cultural Equivalent strategy applied sthirty two (32) times, Transposition strategy applied nine (9) times, Modulation strategy applied seven (7) times, Reduction strategy applied eight (8) times, Expansion strategy applied six (6) times, Couplets strategy applied twelve (12) times, Triplets strategy applied eight (8) times, Quadruplets strategy applied four (4) times, Notes strategy applied two (2) times and Synonymy strategy applied two (2) times. This study concludes that the translation result was appropriate with skopos theory. Keywords: Translation, Skopos, translation strategies, Bilingual children’s storybook.